ANALISIS PERBANDINGAN ABNORMAL RETUR, TRADING VOLUME ACTIVITY DAN HARGA SAHAM PERISTIWA IDUL FITRI PADA PERUSAHAAN LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023 - Putra, Sony Setiawan Dwi; Damayanti, Damayanti (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to determine whether there are differences in stock returns, abnormal stock returns, and trading volume activity before and after the Eid al-Fitr event in companies listed in the LQ 45 index on the Indonesia Stock Exchange for the period 2021-2023. The sampling method used is purposive sampling, with data obtained from 20 observed companies. The parametric test used is the paired sample t-test. The results of the partial test (paired sample t-test) show no significant difference in the trading volume activity variable when comparing 7 days before and 7 days after the Eid al-Fitr event. However, the stock return and abnormal return variables show a significant difference between the 7 days before and 7 days after the Eid al-Fitr event.